Distinguishing Relapse From Reinfection With Whole-Genome Sequencing in Recurrent Pulmonary Tuberculosis: A Retrospective Cohort Study in Beijing, China - Du, Jian; Li, Qing; Liu, Min; Wang, Yufeng; Xue, Zhongtan; Huo, Fengmin; Zhang, Xuxia; Shang, Yuanyuan; Li, Shanshan; Huang, Hairong; Pang, Yu (Frontiers in Microbiology, 2021)
Background: Tuberculosis recurrence is still a major problem for the control of tuberculosis, and the cause of the recurrence is still unclear. Methods: We retrospectively recruited 68 pairs of samples of Mycobacterium tuberculosis (MTB) from recurrent TB cases in Beijing Chest Hospital between January 2008 and December 2019. The whole genome sequencing was conducted to analyze single nucleotide polymorphism (SNP) and to identify whether recurrent disease was due to relapse or reinfection. The BACTEC MGIT was performed to compare differences in drug susceptibility profiles between two episodes. Results: 62 (91.2%) out of 68 confirmed recurrence were due to relapse; whereas the remaining 6 (8.8%) were due to reinfection. And there was a strong association between earlier relapse and underlying chronic diseases. In addition, the MTB isolates from non-diabetic patients had a higher mutation rate than those from diabetic patients. A community transmission was also identified in our cohort. Levofloxacin resistance was the most frequently observed drug resistance for 12.9% relapse cases. Conclusions: The relapse of a previous episode in Beijing. The underlying chronic diseases are associated with an earlier TB relapse. MTB isolates were more prone to develop levofloxacin resistance than moxifloxacin resistance after FQ exposure. The patients at high-risk for relapses deserve more careful investigation.